Earlier onset of delta-retrovirus-induced leukemia after splenectomy. - Arnaud Florins; Michal Reichert; Becca Asquith; Amel-Baya Bouzar; Geneviève Jean; Carole François; Agnieszka Jasik; Arsène Burny; Richard Kettmann; Luc Willems (PLoS ONE)
Infection by delta-retroviruses such as human T-lymphotropic virus type 1 (HTLV-1) and bovine leukemia virus (BLV) is mostly asymptomatic. Indeed, only a minority (<5%) of delta-retrovirus infected hosts will develop either lymphoproliferative or neurodegenerative diseases after long latency periods. In fact, the host immune response is believed to tightly control viral replication but this assumption has not been definitely proven in vivo. Here, we provide direct experimental evidence demonstrating that integrity of the spleen is required to control pathogenesis. In the BLV model, we show that asplenia decreases efficiency of the immune response and induces an imbalance in cell dynamics resulting in accelerated onset of leukemia. These observations enlighten a potential threat in splenectomized HTLV-1 carriers and justify a regular preventive evaluation.